Intracranial Infections in Neurological Surgery: The Changes of Circular RNA Expression and Their Possible Function Mechanism. - Niu, Jiangtao; Xu, Hongqi; Yang, Bo (BioMed Research International, 2020)
Background and Objective. Circular RNA (circRNA) often has high stability and has been widely studied as diagnostic markers in many diseases, including neurodegenerative disorders, diabetes, and various types of cancers. In this study, circRNA was evaluated as a diagnostic marker for central nervous system infection in neurological surgery. Methods. circRNA expression was analysed in six cerebrospinal fluid (CSF) samples from three patients of the infectious and noninfectious phases using an Arraystar Human circRNA Array. Differentially altered circRNAs were validated by quantitative real-time polymerase chain reaction (qRT-PCR) in the 66 CSF samples of 33 patients of the infectious and noninfectious phases. t -test was used for statistical analysis. A bioinformatics analysis was employed to investigate the function mechanism of the circRNAs. Results. Firstly, 142 circRNAs were found significantly different in 6 CSF samples of the infection and noninfection phases of 3 patients. Fourteen circRNAs with the top largest fold changes were chosen from the 142 circRNAs for PCR validation in the same 6 CSF samples of 3 patients. Three circRNAs were selected to be validated in 60 CSF samples of 30 patients using the PCR test. In infection CSF, an upregulated hsa_circRNA_402632 and downregulated hsa_circRNA_008636 and hsa_circRNA_405481 were confirmed by PCR test. A bioinformatics analysis was used to investigate the function mechanism of the 3 circRNAs. hsa_circRNA_402632 is enriched in the insulin resistance pathway, the FoxO and AMPK signaling pathways are the most important pathways for hsa_circRNA_008636 gene expression, and hsa_circRNA_405481 is enriched in the endometrial cancer signaling pathway, Fc epsilon RI signaling pathway, and TGF-beta signaling pathway. Conclusions. hsa_circRNA_402632, hsa_circRNA_008636, and hsa_circRNA_405481 may be potential diagnostic markers for central nervous system infection after neurological surgery.